2008
DOI: 10.1055/s-2007-989395
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Pacing Modes on Left Ventricular Function Following Cardiopulmonary Bypass

Abstract: In the majority of patients with reduced LV function, temporary biventricular pacing improves CO and arterial blood pressure after surgery, especially when LV dilatation is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
0
6
0
2
Order By: Relevance
“…Importantly, this is not associated with changes in myocardial energy demand (21), unlike most inotropic agents, which improve contractility at the expense of increased oxygen consumption and energy store depletion (29). Acute functional benefit without increased energy cost makes BiVP an excellent option for treatment of postoperative ventricular failure, and initial studies have shown its utility after cardiac surgery (14,20,23,24,33).…”
mentioning
confidence: 99%
“…Importantly, this is not associated with changes in myocardial energy demand (21), unlike most inotropic agents, which improve contractility at the expense of increased oxygen consumption and energy store depletion (29). Acute functional benefit without increased energy cost makes BiVP an excellent option for treatment of postoperative ventricular failure, and initial studies have shown its utility after cardiac surgery (14,20,23,24,33).…”
mentioning
confidence: 99%
“…They concluded that only 9 of the 13 publications, resulted in significant increases of cardiac index,up to 22% with BiVP or AR-LVP. Tanaka et al and others [18,22,23] observed greatest benefits in patients with low EF and wide QRS complex. Whereas others, report no significant hemodynamic improvement with these pacing modes or even no adverse effects with RA-RVP in populations with normal ventricular function [19-21].…”
Section: Discussionmentioning
confidence: 99%
“…The strategy for perioperative optimization, by means of LVP or BiVP using a LV basal cathodal electrode and adequate adjustments of AVD and VVD if feasible, is gaining progressive acceptance, to improve CO perioperatively, particularly in cases with depressed EF and LBBB [11,13,18,23]…”
Section: Discussionmentioning
confidence: 99%
“…The effects of temporary BiVP after cardiac surgery and benefits in low output states are not well defined [6-13]. Benefits of BiVP optimization in this setting are unknown [14-23].…”
Section: Introductionmentioning
confidence: 99%